1985
DOI: 10.1256/smsqj.46906
|View full text |Cite
|
Sign up to set email alerts
|

An airborne study of vertical structure and microphysical variability within a small cumulus

Abstract: SUMMARYOn 27 July 1981, as part of the CCOPE experiment, the University of Wyoming King Air research aeroplane made penetrations at six levels ranging from 590mb (-4.9"C) to 770mb (7.2"C) through a nonprecipitating, unglaciated cumulus cloud whose top was at about 560mb (-7°C) and base about 780mb (8°C). The entire flight sequence-from the top downwards-took about six minutes. Principal measurements were of droplet size distribution N ( d ) , number concentration N and liquid water content L , measured at 10Hz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The simulated approximately constant-with-height mean cloud droplet concentration is broadly consistent with many cloud observations, including observations of Montana cumuli reported in Blyth and Latham [1985 (their Table 2 and Fig. 7), 1991 (their Table 1)] and RICO trade-wind cumuli discussed in Gerber et al [2008 (see their Table 3 in particular)] and in Arabas et al (2009, their Fig.…”
Section: B Cloud Droplet Concentration and In-cloud Activationsupporting
confidence: 85%
“…The simulated approximately constant-with-height mean cloud droplet concentration is broadly consistent with many cloud observations, including observations of Montana cumuli reported in Blyth and Latham [1985 (their Table 2 and Fig. 7), 1991 (their Table 1)] and RICO trade-wind cumuli discussed in Gerber et al [2008 (see their Table 3 in particular)] and in Arabas et al (2009, their Fig.…”
Section: B Cloud Droplet Concentration and In-cloud Activationsupporting
confidence: 85%
“…Observations of vertical air motions in shallow clouds are typically an order of magnitude higher (e.g., Warner 1977;Blyth and Latham 1985;French et al 1999;Kollias et al 2001;Damiani et al 2008). As a result, we can use the cloud droplets as a tracer of the vertical air motion in fair-weather cumuli.…”
Section: Methodsmentioning
confidence: 99%
“…Yum and Hudson [] also convincingly showed that not only in the SCMS cumulus clouds but also in the stratocumulus clouds measured during several other aircraft campaigns, the correlation between droplet concentration and mean diameter was positive in a large portions of the data sets. This apparent lack of evidence for so‐called superadiabatic droplets [ Blyth and Latham , ] in diluted cloud parcels seems to suggest that mixing of entrained air may not generally promote droplet growth.…”
Section: Introductionmentioning
confidence: 96%